GENERAL PATTERN OF EARTHQUAKES DISTRIBUTION ON THE TERRITORY OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
Based on catalog of Survey for Seismic Protection MES RA the spatio-temporal distribution of hypocenters and epicenters of earthquakes of the territory of Armenia was studied and was offered appropriate conclusions. Data were handled by using Z-map program.
Keywords: earthquake; hypocenter; epicenter